A measureless peril : America in the fight for the Atlantic, the longest battle of World War II - Snow, Richard, 1947- (Scribner, 2010)
In "A Measureless Peril," the historian Richard Snow captures all the drama of the merciless contest between the quickly built U.S. warships and the ever-more cunning and lethal U-boats that controlled the sea lanes of the Atlantic during WWII.